In vitro studies of α-TCP and β-TCP produced from Clinocardium ciliatum seashells - Sahin, Yesim Muge; Orman, Zeynep; Yucel, Sevil (SPRINGER, 2020)
In this study, alpha-TCP and beta-TCP were successfully produced via a mechanochemical method from aragonite structures, Clinocardium ciliatum seashells, at 850 degrees C, 1000 degrees C, and 1200 degrees C sintering temperatures. The characterization of the obtained materials was carried out via FT-IR, SEM/EDX, BET, XRD, ICP-OES analysis. Samples were soaked for 21 days in simulated body fluid (SBF) for a bioactivity test. Additionally, MTT assay was applied to determine the cell viability of samples. Bioactivity in vitro tests showed that bone-like hydroxyapatite formed when the alpha-TCP and beta-TCP were soaked in SBF. TCP bioceramics had a noncytotoxicity effect on SAOS-2 osteoblast-like cells and cell viability increased in 1 to 7 days. The produced bioceramics have ideal pore sizes and properties that are suitable for supporting biological activities. Tris-HCl buffer solution was used to obtain the level of biodegradation. It was seen that alpha-TCP exhibited better dissolution features than beta-TCP.
Keywords: Bioactivity; Bone regeneration; SBF; Seashell; TCP; Tris; MECHANICAL-PROPERTIES; PHOSPHATE SCAFFOLDS; COWRIE; Materials Science